(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the "lingua-cultural" problems of translation, highlighting the challenges translators face when attempting to convey not only the linguistic meaning but also the cultural context embedded in language. Key topics discussed include the difficulties of translating idiomatic expressions, cultural references, untranslatable words, conceptual differences between cultures, and the impact of language structure on meaning. The article emphasizes the importance of cultural sensitivity and contextual understanding in the translation process, noting that successful translation goes beyond a literal word-for-word approach. The conclusion underscores the ongoing relevance of human translators in overcoming these challenges, as they bridge cultural gaps and ensure effective communication across languages